The gardener of Lashkar Gah : a true story of the Afghans who risked everything to fight the Taliban - Brown, Larisa (Bloomsbury Continuum, 2023)
"The 20-year war fought by the US and its allies in Afghanistan is the longest war of the 21st century. It brought opportunity and tragedy for those who were forced to live through it. The abrupt withdrawal of British and American troops in 2021, in what may come to be regarded as one of the worst foreign policy failures of the past hundred years, precipitated the swift recapture of the country by the Taliban. With the withdrawal came upheaval and torment for Afghans who had loyally served alongside NATO forces and were left to fend for themselves at the gates of Kabul airport. This is the story of one such family. The Gardener of Lashkar Gah follows the extraordinary journey of Shaista Gul, a kind man who built a beautiful garden inside a British military base in Helmand Province that became famous as a calm oasis for soldiers with troubled minds. Other members of his family worked for the allies, including his son Jamal, who became an interpreter for the British Army when he was just a teenager. Following the chaotic withdrawal of allied troops, all members of the family suffered. Larisa Brown, Defence Editor for The Times, award-winning journalist and a campaigner for the interpreters of Afghanistan, has spent hundreds of hours talking to members of the Gul family and others in order to tell their remarkable story. In heart-warming and beautifully human prose, she unspools a tale of courage, hope and sacrifice, with the beauty of the garden and the hopes and dreams of the family counterpointed against the violence, anger and chaos raging in Afghanistan at the time. The scandalous betrayal of many of the interpreters and others who worked for the British and American armies is still being revealed. By telling one family's bittersweet experience, The Gardener of Lashkar Gah provides a unique and powerful insight into the devastating effects on ordinary Afghans of the end of the disastrous 'War on Terror'"--Publisher's description.